Penanggulangan Tindak Pidana Pencurian Air Bersih oleh Pelanggan Suatu Penelitian Pada Perusahaan Daerah Air Minum Tirta Mountala Kabupaten Aceh Besar - Ridha Nur Arifa (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2022)
Combating the crime of theft is a countermeasure that focuses more on the repressive nature, namely actions taken after the crime has occurred by enforcing the law and imposing penalties for crimes that have been committed. The theft of clean water violates the provisions of PDAM Tirta Monutala and can also be subject to articles 362 and 406 of the Criminal Code. In the last 5 (five) years, 203 (two hundred and three) cases of theft of clean water have been found by customers, but the perpetrators of the theft have not been investigated by the police but have been administratively resolved. This paper examines countermeasures against the prevention of criminal acts of theft of clean water and obstacl in preventing the factors causing the crime of theft of clean water. Based on the results of the study, it was shown that the completion of the criminal case of theft of clean water at PDAM Tirta Mountala, Aceh Besar District, was that the perpetrators of the theft were not investigated by the police but were resolvedpeacefully by PDAM Tirta Mountala Aceh Besar with customers.